Preparation, characterization, and thermal degradation of polyimide(4–aminophenyl sulfone/3, 3ʹ, 4, 4ʹ-Benzophenonetetracarboxylic dianhydride) nanocomposite with S¡0₂, Ag, and montmorillonite nanofillers - Gharayebi, Yadollah (2014)
Among many engineering polymers, aromatic polyimides (PIs) are recognized by their outstanding thermal stability, excellent mechanical, chemical resistance and electrical properties. In order to further properties enhancement of polyimides, many researchers have made great efforts to preparation of polyimide nanocomposites. The focus in this study is the preparation and characterization of a few binary and ternary of novel polyimide nanocomposite films by names of PI/MMT, PI/SiO2, PI/Ag, PI/SiO2-MMT and PI/SiO2-Ag and also investigation of their thermal properties. The prepared nanocomposites were characterized by XRD, FTIR, TEM, SEM, UV-vis and TGA. PI/MMT nanocomposite films were successfully prepared using in-situ polymerization and solution-dispersion techniques. The activation energy and estimated lifetime of the solid-state process were calculated using the Flynn-Wall-Ozawa‘s method and Toop‘s postulation respectively. The TGA results indicated that thermal stability, activation energy values and estimated lifetime for thermal decomposition of prepared PI/MMT nanocomposite films were increased with increase of MMT loading for both techniques which the mentioned parameters are higher for products prepared by in-situ polymerization techniques. In this research, PI/SiO2 hybrid films were successfully prepared via the sol-gel process. The morphological studies indicated that the created SiO2 particles in presence of coupling agent are much smaller than when no coupling agent is used at the same TEOS loading. The thermal studies showed that the thermal stability, activation energy values, estimated lifetime for thermal decomposition and thermal diffusivity increased with increasing of TEOS loading that the values of these parameters are higher for hybrid films prepared in presence of coupling agent. The studies of optical properties indicated that the absorption of samples were increased with increasing of TEOS loading whiles the band gap values were decreased. The effect of SiO2 particles on the dispersion behavior of MMT layers in the PI/SiO2-MMT nanocomposite film, the changes in molecular structure and morphology of the polymer matrix were also characterized during the thermal imidization by means of temporal analyses. Moreover, the synergistic effect of MMT layers and SiO2 particles was investigated. The results showed that in presence of SiO2 particles, rearrangement of dispersed MMT layers in PI/SiO2–MMT nanocomposite film is less than in PI/MMT nanocomposite films during the thermal imidization process. The thermal studies showed that thermal stability, activation energy values and estimated lifetime of the thermal degradation for ternary nanocomposite film are higher than PI/MMT and PI/SiO2 in the same MMT and SiO2 contents. Ultimately, organo–soluble PI/Ag and PI/SiO2/Ag as a ternary nanocomposite materials were successfully synthesized and characterized. Synergistic effect of Ag and SiO2 nanoparticles and kinetic parameters of the degradation processes were also investigated.